2018
DOI: 10.1038/s41598-018-20918-9
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer PdSe2: A promising two-dimensional thermoelectric material

Abstract: Motivated by the recent experimental synthesis of two-dimensional semiconducting film PdSe2, we investigate the electronic and thermal transport properties of PdSe2 monolayer by using the density functional theory and semiclassical Boltzmann transport equation. The calculated results reveal anisotropic transport properties. Low lattice thermal conductivity about 3 Wm−1 K −1 (300K) along the x direction is obtained, and the dimensionless thermoelectric figure of merit can reach 1.1 along the x direction for p-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
143
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 66 publications
15
143
0
1
Order By: Relevance
“…5, together with the lines corresponding to Eqs. (16) and (17), further support our conjucture that the model T Fig. 1(a), dashed lines correspond for the system of Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…5, together with the lines corresponding to Eqs. (16) and (17), further support our conjucture that the model T Fig. 1(a), dashed lines correspond for the system of Fig.…”
Section: Discussionsupporting
confidence: 80%
“…4(a) and 4(b) are numerically close to the approximation given by Eq. (16). Also, the data visualized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal conductivity of monolayer ZrSe 2 and HfSe 2 at room temperature is 1.2 and 1.8 W m −1 K −1 , respectively, which is lower than that of monolayer ZrS 2 , of around 3.2 W m −1 K −1 . Similarly, the thermal conductivity of monolayer PdS 2 is much larger than that of monolayer PdSe 2 . It may be noticed that all these values are from theoretical calculations and more experimental work needs to be carried out to further explore the thermal transport behaviors of these TMDs.…”
Section: Thermal Properties In 2d Semiconductorsmentioning
confidence: 99%
“…1T, 2H, and 3R [11]. Moreover, recent studies [12][13][14][15][16][17][18][19][20] have shown that some TMDs can also exhibit orthorhombic structures, specifically pyrite and marcasite structures.…”
Section: Introductionmentioning
confidence: 99%